Structural, transport and ferroelectric properties of Zn1−xMgxO samples and their local electronic structure. (February 2015) - Kumar, Parmod; Singh, Jitendra Pal; Malik, Hitendra K.; Gautam, Sanjeev; Chae, K.H.; Asokan, K.
Highlights: Structural, Ferroelectric and Transport properties of Zn. Reduction of bond length by the substitution of Mg on Zn site. Increase in the density of occupied state with Mg doping. Abstract: Present work reports the correlation between structural, ferroelectric and transport properties of Zn1− x Mg x O nanoparticles synthesized by sol–gel method, and their local electronic structures. Attributes of structural distortion are observed in Mg doped samples, which was confirmed by Rietveld refinement of X-ray diffraction pattern. Distortion in bond length of the samples occurs with the Mg substitution on the Zn site. The change in bond length (Zn–O) enhances the polarization and hence, an improvement in ferroelectric nature is realized after Mg doping. Moreover, the Mg incorporation increases the electrical resistivity of the samples. These properties are correlated with the local electronic structures provided by X-ray absorption spectroscopy.